2020
DOI: 10.5377/nexo.v33i02.10767
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic seed technology for encapsulation and regrowth of in vitro-derived shoot-tips and somatic embryos of Asparagus officinalis L

Abstract: Apical buds obtained from Asparagus plant vitro culture and somatic embryos obtained from stem cultivation, explants in MS medium supplemented with mg¹ᶫ 1, 2, 4-D and mg¹ᶫ 1 and Kinetin have been used in this research to produce artificial seeds. We encapsulated apical buds and somatic embryo using 2% sodium alginate and calcium chloride to prepare the artificial seeds. We placed artificial seeds at room temperature (about 25 ° C), in the cold, the temperature of 4 ° C and -18 ° C for different times (15,30,60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, the most critical factor influencing the success of a study of synthetic seed technology is storage time. According to the research results Abbasi by increasing the storage time of seeds, the conversion rate decreases [16]. The final condition for the technologies of synthetic seeds is genetic stability.…”
Section: Discussionmentioning
confidence: 97%
“…However, the most critical factor influencing the success of a study of synthetic seed technology is storage time. According to the research results Abbasi by increasing the storage time of seeds, the conversion rate decreases [16]. The final condition for the technologies of synthetic seeds is genetic stability.…”
Section: Discussionmentioning
confidence: 97%
“…A pre-encapsulation culture was used to generate encapsulatable units with a high conversion capacity (70%) in non-sterile soil from somatic embryos. Abbasi et al, [77] mentioned that development of apical buds in vitro from asparagus plant culture and somatic embryos were obtained from stem cultivation were cultivated in MS medium supplemented with 1mg 2,4-D and 1 mg of L -1 Kinetin has the potential to be exploited to create artificial seeds. They found that seeds grown in MS media germinate and convert to seedlings at a faster rate than seeds grown in ½ MS medium.…”
Section: Asparagus (Asparagus Officinalis L)mentioning
confidence: 99%